1967
DOI: 10.1007/bf00486517
|View full text |Cite
|
Sign up to set email alerts
|

The amino acid substitution and some chemical properties of a variant human erythrocyte carbonic anhydrase: Carbonic anhydrase IdMichigan

Abstract: an electrophoretic variant of human red cell carbonic anhydrase I, was purified from erythrocytes obtained from an individual heterozygous for the trait. Primary structural analysis indicates that a lysine residue has exchanged for a threonine residue in the variant enzyme. After isolation, there was approximately 1.8 times as much normal as variant enzyme. Thermostability studies demonstrated that carbonic anhydrase Id was more thermolabile than the normal enzyme. The normal and variant enzymes showed no diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

1968
1968
1977
1977

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 35 publications
0
5
0
2
Order By: Relevance
“…This enzyme, representing about 5 o/, of the total red cell carbonic anhydrase, was indistinguishable from human carbonic anhydrase B in terms of its specific activity, amino acid composition and tryptic peptides [43]. In addition, mutants of the B isozyme were accompanied by a corresponding change in A [44]. Consequently, it was concluded that this form of the enzyme resulted from an epigenetic modification of carbonic anhydrase B, possibly as a results of amide group hydrolysis [17].…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme, representing about 5 o/, of the total red cell carbonic anhydrase, was indistinguishable from human carbonic anhydrase B in terms of its specific activity, amino acid composition and tryptic peptides [43]. In addition, mutants of the B isozyme were accompanied by a corresponding change in A [44]. Consequently, it was concluded that this form of the enzyme resulted from an epigenetic modification of carbonic anhydrase B, possibly as a results of amide group hydrolysis [17].…”
Section: Discussionmentioning
confidence: 99%
“…It is also improbable that a genetically determined abnormality of the blood would be highly polymorphic in several discrete feral mouse populations. When techniques were used for their specific detection, electrophoretic analysis of hemoglobin, protein, and ten erythrocytic enzymes showed no obvious differences between B+ and B -airnals.9, 6-18, [32][33][34][35][36] Further support for a LDH controlling gene in mouse erythrocytes comes from phylogenetic data obtained from red cell LDH phenotypes of 26 different rodent species from the three rodent suborders (myomorpha, Sciuromorpha, Hystricomorpha).37 The red cell LDH zymograms of myomorphs show a predominance of A subunits and therefore LDH-5. Both A and B LDH subunits are expressed in sciuromorphs, resulting in all 5 LDH isozymes.…”
Section: *4mentioning
confidence: 99%
“…It is of interest that despite the close proximity of these substitutions, and the fact that a lysyl residue has been substituted in both cases, the quantitative effects appear to be different. That is, the amount of CA Id in the variant hemolysate seems to be lower than the normal CA I (Shows, 1967), whereas in the CA If hemolysate the levels of the normal and variant enzymes appear to be present in approximately equal amounts.…”
Section: Discussionmentioning
confidence: 92%
“…Tryptic digestion was carried out as previously described for the CA Ie Hull and CA Ie Portsmouth variants (Carter et al, 1972), and chymotryptic digestion by the method of Shows (1967). One-dimensional electrophoretic separation of the peptides was carried out in a pyridine-acetate buffer (pH 6.5) for 3 hr at 3000 v. Guide strips were cut out, and the peptides were eluted with either 6 N HC1 or 1 N acetic acid.…”
Section: Peptide Analysismentioning
confidence: 99%